2013
DOI: 10.5543/tkda.2013.84031
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous closure of secundum atrial septal defects in pediatric and adult patients: short- and mid-term follow-up results

Abstract: Our findings showed that percutaneous closure of ASDs is successful in most patients with a low complication rate, and demonstrated that residual shunts do not develop in the majority of patients in the short- and mid-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Mean procedure duration for fluoroscopy-guided percutaneous ASD closure has been reported to range from 40 to 110 minutes, although it should be noted that the definition of total the procedure time varied among studies. [ 9 , 14 , 15 , 17 ] In the present study, procedure time (measured from heparinization to removal of the delivery system) was significantly shorter in the TEE group (21.5 ± 14.6 minutes) than in the fluoroscopy group (28.6 ± 10.9 minutes). Ewert et al [ 41 ] also reported numerically shorter duration for TEE-guided ASD closure (88 minutes) than for conventional fluoroscopy-guided ASD closure (100 minutes), but the difference was not statistically significant ( P = .09).…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Mean procedure duration for fluoroscopy-guided percutaneous ASD closure has been reported to range from 40 to 110 minutes, although it should be noted that the definition of total the procedure time varied among studies. [ 9 , 14 , 15 , 17 ] In the present study, procedure time (measured from heparinization to removal of the delivery system) was significantly shorter in the TEE group (21.5 ± 14.6 minutes) than in the fluoroscopy group (28.6 ± 10.9 minutes). Ewert et al [ 41 ] also reported numerically shorter duration for TEE-guided ASD closure (88 minutes) than for conventional fluoroscopy-guided ASD closure (100 minutes), but the difference was not statistically significant ( P = .09).…”
Section: Discussionmentioning
confidence: 45%
“…Numerous studies have reported the use of fluoroscopy-guided procedures for the percutaneous closure of ASD and most of these studies used fluoroscopy in combination with TEE or TTE. [ 9 , 11 , 12 , 14 , 17 , 21 , 22 ] Previous studies in pediatric patients using procedures guided by both fluoroscopy and TEE or TTE have reported successful implantation rates of 93% to 100%, low complication rates of 0% to 20% (predominantly minor complications), and good long-term outcomes. [ 8 , 10 , 14 , 15 , 17 ] In the present study, the fluoroscopy group showed a successful implantation rate of 100% and the complication rate was 13%, which are in agreement with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations